A Comparative Analysis of Humor as a Strategy for Public Engagement: Analyzing Types of Humor in Political Speeches and Talk Shows - Imran, Aiman; Gul, Samra; Aizaz, Gul (Pakistan Languages and Humanities Review, 2025)
This study aims to explore the use of humor in political speeches and talk shows. Humor is a strategic communication tool which is used both as a persuasive device and a rhetorical shield which allows politicians to adress criticism indirectly and to maintain audience engagement. The study explores the different types of humor including affiliative humor, self-enhancing humor, aggressive humor and self-defeating humor and how these humor functions differently in different situations. The methodology used for this research is qualitative research methodology and discourse analysis which explores humor usage and allows for in-depth exploration of how political figures employ humor as a persuasive and face-saving strategy. Using a discourse analysis framework, this study classifies humor styles and also evaluates their impact on political messaging and public perception. The findings provide a more detailed understanding of humor types and usage of humor. Further studies could also dwell insights into audience reception analysis and can also address the humor analysis in political discourse using a multidisciplinary or multimodal approach.